Coronary heart disease among adult population evacuated from the 30-km zone of the Chernobyl NPP (Descriptive epidemiologic research results). Observation period 1988-2012 - Kapustynskaia, Olga A. (Journal of Education, Health and Sport, 2015)
Kapustynskaia O A. Ишемическая болезнь сердца у взрослого населения, эвакуированного из 30-км зоны чернобыльской АЭС (Результаты дескриптивных эпидемиологических исследований). Период наблюдения 1988-2012 годы = Coronary heart disease among adult population evacuated from the 30-km zone of the Chernobyl NPP (Descriptive epidemiologic research results). Observation period 1988-2012. Journal of Kapustynskaia O A. Ишемическая болезнь сердца у взрослого населения, эвакуированного из 30-км зоны чернобыльской АЭС (Результаты дескриптивных эпидемиологических исследований). Период наблюдения 1988-2012 годы = Coronary heart disease among adult population evacuated from the 30-km zone of the Chernobyl NPP (Descriptive epidemiologic research results). Observation period 1988-2012. Journal of Education, Health and Sport. 2015;5(2):53-65. ISSN 2391-8306. DOI: 10.5281/zenodo.15081 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A53-65 https://pbn.nauka.gov.pl/works/535830 http://dx.doi.org/10.5281/zenodo.15081 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.01.2015. УДК 616-036.22 Ишемическая болезнь сердца у взрослого населения, эвакуированного из 30-км зоны Чернобыльской АЭС (результаты дескриптивных эпидемиологических исследований). Период наблюдения 1988-2012 годы Coronary Heart Disease Among Adult Population Evacuated From the 30-km Zone of the Chernobyl NPP (descriptive epidemiologic research results). Observation Period 1988-2012 О.А. Капустинская OA Kapustynskaia ГУ «Национальный научный центр радиационной медицины НАМН Украины» SI “National Scientific Center of Radiation Medicine of National Academy Medical Science of Ukraine”, Kiev Резюме Определение и анализ динамики уровня заболеваемости взрослого эвакуированного населения на ИБС, включая и отдельные ее формы, с учетом возраста на момент аварии, пола и времени с момента аварии. В статье использованы данные Государственного реестра Украины лиц, пострадавших вследствие Чернобыльской катастрофы (ГРУ) и статистические данные Минздрава Украины о заболеваемости взрослого населения Украины. Исследования проводились в целом по заболеваемости на ИБС, а также по нозологическим формам: стенокардия; инфаркт миокарда; хроническая ИБС. Дескриптивное эпидемиологическое исследование проведено за период 1988-2010 годы. Когорта взрослого эвакуированного населения составила 55022 человека, из них 22056 мужчин и 32966 женщин. Для сравнения использованы статистические данные о заболеваемости взрослого населения Украины. В работе использован также метод внутреннего сравнения, позволяющий оценить достоверность отличий показателей заболеваемости по периодам наблюдения. Анализ проведен по следующим п’яти периодам (1988-1992 гг., 1993-1997 гг., 1998-2002 гг., 2003-2008 гг., 2009-2010 гг.). За результатами 24 летнего медицинского наблюдения установлено, что заболеваемость на ИБС взрослого эвакуированного населения имеет существенные возрастные, половые и временные отличия. Повышение уровня заболеваемости на ИБС независимо от возраста на момент аварии следует отнести на период 12 – 22 года. Пик заболеваемости у лиц, возраст которых на момент аварии составил 40-60 лет, отмечен в третьем периоде наблюдения, т.е. спустя 12-16 лет с момента аварии на ЧАЭС, у лиц, эвакуированных в возрасте 18-39 лет - спустя 17-22 года и сохраняется на таком же уровне в последнем периоде. Спустя 24 года после аварии заболеваемость эвакуированных в возрасте 18-39 лет превышает показатели первого периода в 4 раза, а второго периода - в 3 раза. В возрастной группе 40-60 лет в последний период наблюдения отмечается тенденция снижения. Обращает внимание достаточно высокий уровень заболеваемости на ИБС лиц, возраст которых на момент аварии составил 40-60 лет в первые шесть лет с момента аварии, что, очевидно обусловлено влиянием трех основных факторов: «возраст», «скрининг-эффект» и «психо-социальный стресс». У лиц, эвакуированных в возрасте 18-39 лет, не установлено достоверной разницы в уровне заболеваемости мужчин и женщин, в то время, как у женщин 40-60 лет показатели заболеваемости на ИБС выше по сравнению с мужчинами, за исключением последнего этапа наблюдения. В отношении отдельных форм ИБС можно отметить превалирование хронической ИБС. У лиц, эвакуированных в возрасте 18-39 лет, отмечен более высокий темп роста частоты стенокардии и инфаркта миокарда в сравнении с возрастной группой 40-60 лет. В 2009-2010 гг. уровень заболеваемости этими болезнями у лиц, эвакуированных в возрасте 40-60 лет, почти сравнялся с заболеваемостью начальных этапов наблюдения. Высказано предположение о возможной связи роста частоты ИБС в исследуемом контингенте пострадавших с радиационным облучением и влиянием комплекса факторов нерадиационной природы, связанных и не связанных с последствиями аварии на ЧАЭС, что является задачей дальнейших аналитических эпидемиологических исследований. Ключевые слова: авария на ЧАЭС, взрослое эвакуированное население, заболеваемость, ишемическая болезнь сердца Abstract The determination and analyses of the dynamics of the evacuated adults sickness rate of the coronary heart disease also including its particular types including of age at the time of the accident sex and from the moment of the accident. The materials of the Ukrainian public register of people who suffered from the Chernobyl accident (UPR) and the statistical data of the Ministry of Healthcare about the sickness of the Ukrainian population are used in the article. Subject of inquiry: adult population at the time of the accident avacuated from the 30-km Zone of the Chernobyl APP. Object of research - Coronary heart disease. The research was made on the coronary heart disease in whole and also due to nosological forms: angina pectoris; cardiac infarction; chronic coronary heart disease. Descriptive epidemiologic research was made for the period of 1988-2010 years. The cohort of adult avacuated population constituted 55022 people, 22056 men and 32966 women off them. For the comparison the statistic data about the sickness of adult population of Ukraine were used. In the article was also used the method of inner comparison, which allows to evaluate the credibility of the sickness rate figures difference for the periods of observation. The analisys is carried through following five periods (1988-1992 years, 1993-1997 years, 1998-2002 years, 2003-2008 years, 2009-2010 years). In accordance with the 24-years medical observation was determined that the coronary heart disease incidence of the adult evacuated population has significant differences due to age, sex and time. The increase in the coronary heart disease incidence regardless age at the moment of the accident is to be considered for the period of 12-22 years. The peak of the sickness for those, who were 40-60 at the time of the accident, was registered for the third period of observation, i. e. after 12-16 years from the moment of the accident at the Chernobyl NPP, for those, evacuated at the age of 18-39 – after 17-22 years and remains at the same level in the last period. 24 years later after the accident the rate of sickness of those, evacuated at the age 18-39, surpasses the figures of the first period four times and the second period – 3 times. In the age group of 40-60 years in the last period of observation the decrease is noted. High enough coronary heart disease incidence of those people, whose age at the time of accident was 40-60 at the first six years from the moment of the accident keeps attention, that, obviously, was caused by the influence of three main factors: “age”, “screening-effect” and “psycho-social stress”. For people evacuated at the age of 18-39 the proved difference in the sickness rate of men and women wasn’t stated, whereas the figures of coronary heart disease for women of 40-60 years old are higher in comparison with men with an exception of the last stage of observation. What the particular forms of the coronary heart disease concerns the prevaluating of the cronical coronary heart disease is noted. For the people evacuated at the age of 18-39, was noted the higher frequency growth rate of angina pectoris and cardiac infarction in comparison to the people of age 40-60. In2009-2010 the sickness rate for these diseases for the people evacuated at the age of 40-60 was almost equal to the sickness rate of the first stages of observation. There is the hypothesis about the possible connection between frequency growth rate of coronary heart disease for the contingent of the sufferers with the exposure to radiation among those under observation and the impact of the complex of factors of nonradiation nature connected and not connected to the consequences of the Chernobyl APP accident, which is the task for the further analitical epidemiologic research. Key words: Chernobyl APP accident, adult evacuated population, sickness rate, coronary heart disease